Investigating the simultaneous impact of infrastructure and geographical factors on international trade: Evidence from asian economies - Huizhen Mao; GengHao Cui; Zahid Hussain; Lin Shao (Heliyon, 2024)
Infrastructure and geography are the most important components of international trade. They provide trade-oriented amenities for the trade volume among trading partners. Thus, this study assesses the simultaneous impact of infrastructure and geographic factors on trade in Asian economies from 2004 to 2020. This work contributes to the existing literature by exploring the significance of infrastructure and geography in international trade. Furthermore, this research seeks to determine whether these factors have complementary or simultaneous effects. To examine these aspects, the augmented gravity model and cross-sectional autoregressive distributed lags are used in the current model. Then, the multilateral resistance terms are corrected. Results reveal that infrastructure has a significant and positive impact on trade. More precisely, transport infrastructure, communication infrastructure, financial infrastructure, and border-transport efficiency are productive influencers for trade over a certain period. Notably, the simultaneous impacts of infrastructure and geographic factors can lead to the deterioration of trade volume. The policy implications and future research direction of this study suggest that economies should improve infrastructure and geographic factors through gross domestic product.